ENHANCING LANGUAGE LEARNING WITH SUGGESTOPEDIA - Qarshiyeva Shohista Doniyor qizi (Bright Mind Publishing, 2025)
Traditional language teaching methods often lead to disengagement, anxiety, and limited student interaction, particularly among beginner EFL learners. To address these challenges, this article explores the effectiveness of Suggestopedia, a holistic and humanistic approach to language learning that integrates music, relaxation, and positive suggestion. The method focuses on creating a low-stress, emotionally supportive classroom environment where students can absorb language naturally and confidently. Practical activities such as dramatized reading, music-based vocabulary practice, role play, and creative storytelling were implemented in beginner EFL classrooms. The results showed a noticeable improvement in student motivation, participation, vocabulary retention, and grammatical accuracy. Learners reported feeling more relaxed, confident, and engaged during lessons. Suggestopedia not only enhances language proficiency but also fosters creativity and enjoyment in the learning process. The study concludes that Suggestopedia is a highly effective alternative to traditional methods and can play a valuable role in improving overall language learning outcomes.
Keywords: Suggestopedia, language learning, EFL (English as a Foreign Language), vocabulary retention, student engagement, grammar improvement, emotional support in learning.